Pembiayaan Berbasis Teknologi Informasi (Fintech) yang Berdasarkan Syariah - Achmad Basori Alwi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
In the era of the digital economy, societies develop innovation of service in the activities of financing that one of them is characterized by the existence of the provision of Services and loan borrowing money based information technology assessed against development and contribute to the national economy. One of them, financing system with agreement that the parties who proposed financing by parties who provide funding online. Financing through service loan borrowing money based on information technology (fintech) in Shariah. As for the reason of syariah-based fintech service launched is to accommodate users who want sharia-based loan borrowing transactions. Sharia-based fintech services in addition to providing supply and of different schemes of existing services (conventional), also provided a limitation of certain restrictions against the use of the funds given by investors or lenders. User request services of Sharia-based fintech rising currencies with the market share of service users from moslem majority in Indonesia was pushing sharia-based Fintech compulsory Service meet rules in business transaction in sharia.